Analysis of diagrams in the kinetic gas theory materials in high school physics textbooks: a content analysis - Agustina, Remilda; Gumilar, Surya; Sari, Lasmita (Insitut Pendidikan Indonesia, 2023)
The theory of gas kinetics material studies objects that are abstract in nature. Therefore, its learning requires visual representations capable of visualizing these abstract objects, one of which is diagrams. The presence of diagrams in high school physics textbooks is considered important to aid the learning process. This research aims to determine the distribution of diagram categories, trends in diagram usage, and teachers’ perceptions of diagram usage in the Theory of Gas Kinetics material in high school physics textbooks with a descriptive quantitative research design. The research results show the distribution of diagram categories with the highest percentage in each analyzed book being the glossary image category, accounting for an overall percentage of 45%. The usage trends of each diagram category tend to fluctuate from year to year. Based on the findings of this research, teachers’ perceptions of diagram usage in the Theory of Gas Kinetics material have three main themes: diagrams are important as learning aids to make lessons more interesting and to represent the identity of science, especially physics; the use of diagrams depends on teachers’ needs; and diagrams help students understand the text and present physics concepts more specifically.